LINCing Nuclear Mechanobiology With Skeletal Muscle Mass and Function - van Ingen, Maria J. A.; Kirby, Tyler J. (Frontiers in Cell and Developmental Biology, 2021)
Skeletal muscle demonstrates a high degree of adaptability in response to changes in mechanical input. The phenotypic transformation in response to mechanical cues includes changes in muscle mass and force generating capabilities, yet the molecular pathways that govern skeletal muscle adaptation are still incompletely understood. While there is strong evidence that mechanotransduction pathways that stimulate protein synthesis play a key role in regulation of muscle mass, there are likely additional mechano-sensitive mechanisms important for controlling functional muscle adaptation. There is emerging evidence that the cell nucleus can directly respond to mechanical signals (i.e., nuclear mechanotransduction), providing a potential additional level of cellular regulation for controlling skeletal muscle mass. The importance of nuclear mechanotransduction in cellular function is evident by the various genetic diseases that arise from mutations in proteins crucial to the transmission of force between the cytoskeleton and the nucleus. Intriguingly, these diseases preferentially affect cardiac and skeletal muscle, suggesting that nuclear mechanotransduction is critically important for striated muscle homeostasis. Here we discuss our current understanding for how the nucleus acts as a mechanosensor, describe the main cytoskeletal and nuclear proteins involved in the process, and propose how similar mechanoresponsive mechanisms could occur in the unique cellular environment of a myofiber. In addition, we examine how nuclear mechanotransduction fits into our current framework for how mechanical stimuli regulates skeletal muscle mass.